2006
DOI: 10.1007/s00213-006-0344-0
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the central effects of ketamine in the rat using pharmacological MRI

Abstract: Ketamine produced localised dose-dependent alterations in BOLD MR signal, which correlate with the pharmacodynamic profile of the drug. These results can be, at least, partially substantiated with complementary techniques but consideration must be given to the input function applied to the MR signal and the use of anaesthesia during phMRI experimentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
33
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 87 publications
(93 reference statements)
8
33
0
Order By: Relevance
“…Although phMRI has been frequently used in preclinical and clinical settings, the number of examples in which phMRI responses are translated between rodents and humans is limited to a few cases. Of interest, ketamine phMRI infusion responses have been measured in naive rats (Littlewood et al, 2006;Chin et al, 2011) and healthy human subjects (De Simoni et al, 2012); robust responses were detected in the cingulate, frontal cortex, and hippocampal formation in both species (Bifone and Gozzi, 2012). Similarly, a highly convergent phMRI signature has been observed between rodents (Liu et al, 2007) and humans (Leppa et al, 2006) after acute remifentanil administration, in which activation was present in brain structures, such as the striatum, thalamus, hippocampus, and cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Although phMRI has been frequently used in preclinical and clinical settings, the number of examples in which phMRI responses are translated between rodents and humans is limited to a few cases. Of interest, ketamine phMRI infusion responses have been measured in naive rats (Littlewood et al, 2006;Chin et al, 2011) and healthy human subjects (De Simoni et al, 2012); robust responses were detected in the cingulate, frontal cortex, and hippocampal formation in both species (Bifone and Gozzi, 2012). Similarly, a highly convergent phMRI signature has been observed between rodents (Liu et al, 2007) and humans (Leppa et al, 2006) after acute remifentanil administration, in which activation was present in brain structures, such as the striatum, thalamus, hippocampus, and cingulate cortex.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have used SPM techniques in rats with different imaging modalities: autoradiographic iodoantipyrine [30][31][32][33][34], fMRI [35][36][37][38][39][40], and FDG-PET [20,41,42]. Two PET studies used a standardization according to a custom digital template matched to a highresolution microMRI image in Paxinos orientation [41,42].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, N-methyl-D-aspartate (NMDA) antagonists, such as phencyclidine (PCP) or ketamine, can induce symptoms that mimic psychosis in healthy volunteers and exacerbate symptoms in schizophrenic patients (Krystal et al, 1994;Lahti et al, 1995). Using in vivo imaging, Littlewood et al (2006) demonstrated that ketamine increased BOLD signals in the frontal, hippocampal, cortical, and limbic areas with the largest activations observed in the retrosplenial cortex and hippocampus. In addition, it was found that pretreatment of glutamatergic agents seemed to globally modulate rCBV changes in rats challenged with PCP (Gozzi et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was found that pretreatment of glutamatergic agents seemed to globally modulate rCBV changes in rats challenged with PCP (Gozzi et al, 2008). It is intriguing that ketamine, which can induce psychomimetic symptoms or behavioral aberrations (Moghaddam et al, 1997;Nishizawa et al, 2000;Becker and Grecksch, 2004), produced significant changes of brain activity in several cortical, hippocampal, and midbrain regions in animals and humans (Lång-sjö et al, 2003;Holcomb et al, 2005;Honey et al, 2005;Littlewood et al, 2006). A central translational perspective is to conduct the preclinical studies in a way that would allow the study in humans.…”
Section: Introductionmentioning
confidence: 99%